Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230806 ZenodoArchiveConcept: 14230805 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1062 10.53832/edtechhub.1074
Keywords: _r:AddedByMyEducationEvidence

Rapport de l’échange de connaissances - Koomar, Saalim; Rasolohery, Hasiniavo; Oojorah, Avinash; Udhin, Waaiza (EdTech Hub, 2025)
This is a report on a knowledge exchange visit between the Ministry of National Education of Madagascar and the Mauritius Institute for Education. The visit focused on sharing lessons and discussing ongoing projects related to technology in education. Key objectives included presenting successes and challenges of distance learning, discussing pedagogical design and digital platforms, and exploring long-term collaboration. School visits provided insights into technology integration in classrooms and teacher experiences. The report details the workshop's activities, participants, and key points, emphasising the importance of data-driven projects, feedback mechanisms, and continuous evaluation. Recommendations for future collaboration include short-term actions like remote communication and training, medium-term initiatives like co-presenting at conferences and personnel exchange, and long-term goals like co-applying for regional research projects. Keywords: teacher professional development; Madagascar; Moodle; knowledge exchange; EdTech; pedagogy Ce rapport porte sur une visite d’échange de connaissances entre le Ministère de l’Éducation Nationale de Madagascar et le Mauritius Institute for Education. La visite avait pour objectif de partager les enseignements tirés et de discuter des projets en cours liés aux technologies éducatives. Les principaux objectifs comprenaient la présentation des succès et des défis de l’apprentissage à distance, la discussion sur la conception pédagogique et les plateformes numériques, ainsi que l’exploration d’une collaboration à long terme. Les visites d’écoles ont permis d’observer l’intégration des technologies en classe et l’expérience des enseignants. Le rapport détaille les activités de l’atelier, les participants et les points clés, en mettant l’accent sur l’importance des projets basés sur les données, des mécanismes de retour d’information et de l’évaluation continue. Les recommandations pour une future collaboration incluent : Actions à court terme : communication et formation à distance; Initiatives à moyen terme : co-présentation lors de conférences et échanges de personnel; Objectifs à long terme : candidature conjointe à des projets de recherche régionaux. Mots clés: formation pédagogique; Madagascar; Moodle; échange de connaissances; technologie dans l’éducation; pédagogie An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230830 ZenodoArchiveConcept: 14230829 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1061 10.53832/edtechhub.1075
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence